KETERAMPILAN SHOOTING FREETHROW - Septiana, Rama Adha (Jurnal Olahraga, 2016)
The purpose of this study was to determine the relationship between wrist flexibility, eye-hand coordination, and confidence in basketball freethrow shooting skills. The research method used in this study is correlational. Samples were 28 students who took part in student activity units. The independent variables are wrist flexibility (X1), hand coordination (X2), and confidence (X3). While the dependent variable is shooting skills on basketball (Y). The results showed that first there was a significant relationship between X1 and Y, the correlation coefficient was 0.530 with a significance value of 0,000. Second, there was a significant relationship between X2 and Y, the correlation coefficient was 0.528 with a significance value of 0,000. Third, there is a significant relationship between X3 and Y, the correlation coefficient is 0.566 with a significance value of 0.0002. Fourth, there is a significant relationship between X1, X2, X3 together with Y, the correlation coefficient is 28.799 and 2.725 Based on the results of the study it can be concluded that wrist flexibility, eye-hand coordination, and self-confidence are significantly related to basketball freethrow shooting skills. For this reason, athletes must do exercises that can increase wrist flexibility, eye-hand coordination, and high confidence in order to improve basketball freethrow shooting skills.